Evaluation of the Active constituents, Antioxidant, and Antimicrobial Activities of Iraqi Euonymus Japonicus leaves using Ethyl Acetate Extract - Khalaf, Rasha A.; Abdul-Jalil , Thukaa z. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Euonymus japonicus is one species of celastraceous family used as decorative plant and traditional Chinese medicine. The lack of information about the main active constituents and the possible biological activities of Iraqi Euonymus japonicus leaves considered as a motivation to start this in vitro studyObjectives: to identify the phytochemical components and to evaluation antioxidant and antimicrobial activities Material and Methods: The chemical composition of Iraqi Euonymus japonicus leaves was identified and analyzed using the Reversed-Phase High-Performance Liquid Chromatography approach and the antioxidant properties were measured by free radical - scavenging assay DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate). Furthermore, the antibacterial properties were evaluated via agar well diffusion method against two pathogenic bacteria Staphylococcus- aureus, E. coli and Candida albicans.Results: The results showed that the main active constituents of Euonymus japonicus leaves in ethyl acetate fraction were Naringenin, vitexin, Kaempferol, Apigenin and quercetin respectively.in addition  antioxidant activity of   ethyl-acetate fraction had the greatest antioxidant activity with the IC50 value 54.89 μg /mL while the highest antimicrobial efficacy of the ethyl acetate extract (3.125, 6.25, 12.5, 25, 50 and 100 µg/ml) was demonstrated by the inhibitory zones (12-19 mm for Staphylococcus- aureus,16-20 mm for E. coli,16-21 mm for candida albicans) compared with positive control Augmentin (19 mm) and ketoconazole (16mm) respectivelyConclusion:   The first identification of antimicrobial and antioxidant activity of E. japonicus in vitro ,show this plant have highest activity in compared to standard, this activity related to the  polyphenolic compound .